Developing a Research Framework: Lessons from Malaysia's Hotel Industry - Yashidevan, Saththasivam; Mohammad, Yazam Sharif (2015)
this research attempts to analyze the effect of employee motivation on work performance in hotels in Malaysia.The elements used under employee motivation are pay, job security, working environment, career development and recognition. Work performance is the dependent variable whereas employee motivation is the independent variable. The purpose of conducting the research is to solve the research problem, which is employees are the most important factor in the hotel industry. The services offered by employees are the reasonfor tourist to continue to flood the country. In order for employees to continue offering good services, factors that can keep them motivated to perform are of utmost important. The government realizes the importance of ‘people’ and concerns were raised about whether the hotel industry will be able to retain talents and obtain good work performance through attractive salaries. Therefore, this research is undertaken to understand the influence of employee motivation on work performance and to understand this. This research intends to identify the factors that have effect on work performance.